Patient and tumor characteristics predictive of an elevated hepatopulmonary shunt fraction before radioembolization of hepatic tumors. Issue 9 (September 2016) - Yerubandi, Vijay; Ronald, James; Howard, Brandon A.; Suhocki, Paul V.; James, Olga G.; Wong, Terence Z.; Kim, Charles Y.
Abstract : Objective: To determine whether any patient or hepatic tumor characteristics are predictive of hepatopulmonary shunt fraction when performed before radioembolization. Materials and methods: A retrospective review was performed on 190 patients who underwent preradioembolization hepatic arteriography with calculation of hepatopulmonary shunt fraction using technetium-99m-labeled macroaggregated albumin perfusion scintigraphy. Patient and tumor characteristics including imaging features were reviewed for correlation with absolute shunt fraction, shunt fraction greater than 10%, and shunt fraction greater than 20%. Results: Most tumor types showed some cases of elevated shunt fraction greater than 10%. Six patients had a shunt fraction greater than 20%: four were hepatocellular carcinoma and two were neuroendocrine tumor metastases. Univariate analysis showed that dominant tumor diameter, hepatic tumor burden, vascular invasion, hepatic venous invasion, and hypervascularity on angiography were associated with a shunt fraction greater than 10%. Only dominant tumor diameter and vascular invasion were associated with a shunt fraction greater than 20%. On multivariate analysis, only tumor diameter (odds ratio 1.2) and hepatic venous invasion (odds ratio 23.0) were associated independently with an increased shunt fraction greater than 10%. Conclusion: Multiple patient and tumor-related characteristics were significantly correlated with the hepatopulmonary shunt fraction on univariate analysis. However, on multivariate analysis, only the dominant tumor diameter and presence of hepatic venous invasion were associated independently with a greater than 10% shunt fraction.